2021
DOI: 10.1038/s41598-020-80637-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress and corticosterone exacerbate alcohol-induced tissue injury in the gut-liver-brain axis

Abstract: Alcohol use disorders are associated with altered stress responses, but the impact of stress or stress hormones on alcohol-associated tissue injury remain unknown. We evaluated the effects of chronic restraint stress on alcohol-induced gut barrier dysfunction and liver damage in mice. To determine whether corticosterone is the stress hormone associated with the stress-induced effects, we evaluated the effect of chronic corticosterone treatment on alcoholic tissue injury at the Gut-Liver-Brain (GLB) axis. Chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 78 publications
(91 reference statements)
6
56
0
Order By: Relevance
“…Numerous studies have shown that alcohol use alters the abundance and composition of gut microbiota 29–31 . Our recent study demonstrated that corticosterone further modulates alcohol‐induced alteration of gut microbiota in mice 15 . However, the precise mechanism involved in alcohol‐ or stress‐induced dysbiosis of gut microbiota is poorly defined.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous studies have shown that alcohol use alters the abundance and composition of gut microbiota 29–31 . Our recent study demonstrated that corticosterone further modulates alcohol‐induced alteration of gut microbiota in mice 15 . However, the precise mechanism involved in alcohol‐ or stress‐induced dysbiosis of gut microbiota is poorly defined.…”
Section: Discussionmentioning
confidence: 97%
“…9,36,37 Restraint stress and alcohol feeding in rodents elevate plasma corticosterone. 15,38 Glucocorticoids play a role in neuroimmune functions 39,40 ; however, their role in alcohol-induced peripheral tissue injury is unclear. Cortisol and corticosterone actions are mediated by the glucocorticoid receptor (GR).…”
Section: Introductionmentioning
confidence: 99%
“…Shukla et al (2021) proposed the gut-liver-brain (GLB) axis hypothesis and reported that chronic stress and corticosterone can exacerbate alcoholinduced mucosal barrier dysfunction, endotoxemia, and the systemic alcohol response. The authors also demonstrated that gut microbiota modulation probably plays a key role in oxidative stress induced by alcohol [67]. In addition, the metabolites of the gut microbiota, including lipopolysaccharides, ethanol, ammonia, and acetaldehyde, also promote the development of chronic hepatitis [68].…”
Section: Rbe Exerted Protective Effects Against Liver Damage In Male Offspring Rats Via Alterations Of Gut Microbiotamentioning
confidence: 94%
“…DNA was extracted with TRIzol (Invitrogen, Carlsbad, CA, USA) as per the manufacturers' instructions. 16S ribosomal RNA was analyzed by qPCR for different bacterial phyla or species using SYBR Green/ROX master mix (Qiagen) in an Applied Biosystems QuantStudio6 FlexReal-Time PCR instrument (Norwalk, CT, USA) as described in our published papers [37,38]. Primer sequences for 16S ribosomal RNA genes for Bacteroidetes, Firmicutes, Bifidobacteria, and Lactobacillus were detailed in Table S1.…”
Section: Microbiome Analysismentioning
confidence: 99%
“…Immunofluorescence staining in the colon was performed as described previously [38,40]. Colon sections were examined for components of the inflammasome (NLRP3, ASC, and caspase-1), F-actin, tight junction (TJ) proteins occludin and ZO1, and adherens junction (AJ) proteins E-cadherin, and β-catenin by confocal microscopy as described previously.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%